2012
DOI: 10.1109/tbme.2012.2204054
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Measurement of Postmortem Tissue Changes in the Crystalline Lens by Brillouin Spectroscopy and Confocal Reflectance Microscopy

Abstract: Use of Brillouin spectroscopy in ophthalmology enables noninvasive, spatially resolved determination of the rheological properties of crystalline lens tissue. Furthermore, the Brillouin shift correlates with the protein concentration inside the lens. In vitro measurements on extracted porcine lenses demonstrate that results obtained with Brillouin spectroscopy depend strongly on time after death. The intensity of the Brillouin signal decreases significantly as early as 5 h postmortem. Moreover, the fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…This result was confirmed by the ex vivo experiments, where we compared Brillouin moduli to shear moduli measured by traditional gold-standard shear rheometry. Our result is consistent with findings based on previous Brillouin scattering experiments, 21 , 24 , 29 , 44 , 45 bubble-based acoustic radiation force, 19 , 46 and conical probe indentation, 18 in which the elastic modulus in the nucleus was always larger than in the cortex in both animals and human samples. However, these results do not agree with other experiments using spinning platforms and localized small probes in which the nucleus was found to be softer than the cortex in human lenses at ages up to 30 to 50 years old.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result was confirmed by the ex vivo experiments, where we compared Brillouin moduli to shear moduli measured by traditional gold-standard shear rheometry. Our result is consistent with findings based on previous Brillouin scattering experiments, 21 , 24 , 29 , 44 , 45 bubble-based acoustic radiation force, 19 , 46 and conical probe indentation, 18 in which the elastic modulus in the nucleus was always larger than in the cortex in both animals and human samples. However, these results do not agree with other experiments using spinning platforms and localized small probes in which the nucleus was found to be softer than the cortex in human lenses at ages up to 30 to 50 years old.…”
Section: Discussionsupporting
confidence: 93%
“… 18 , 19 Ex vivo rheological assessment is also compounded by postmortem changes of the structural and mechanical properties of the lens tissue. 20 , 21 …”
mentioning
confidence: 99%
“…This observation can be associated with residual effects of cataract formation, or overall changes in lens elasticity after 6 h of storage, for example, the loss of crystalline proteins after storage. 54 Previous work has shown that the duration of heating can also increase the elasticity of the lens. 50 When human lenses were heated for 4 h, the shear modulus was .…”
Section: Discussionmentioning
confidence: 99%
“…6). Since the reported value of for the porcine lens is 2.5-3.0 GPa, 46 the optimal value of G is e®ectively independent of as long as the /G ratio exceeds 100. This approach was previously adopted by Burd et al, who¯xed the ratio of bulk modulus to shear modulus at 100 for all simulations.…”
Section: Resultsmentioning
confidence: 99%